Reliability of the Turning Point Core Trainer as a measure of rotational angles and velocities - Brown, J.; Bennion, R.; Hicks-Little, C. (Journal of Fitness Research, 2015)
Introduction: The x-factor is considered an important measure in rotational sports such as golf and is typically assessed using three-dimensional motion capture analysis. Due to equipment costs and lengthy time periods to analyse measurements it is not practical for coaches. Although three-dimensional motion capture analysis is recognised as the gold standard, a cheaper and quicker tool is needed to evaluate such measurements. The Turning Point Core Trainer (TP) is a device designed to measure the x-factor and angular velocities of the upper torso and hips; however, data regarding reliability of the TP is lacking. The purpose of this study was to examine between session reliability of the TP as a measure of the x-factor and angular velocity of the upper torso (SAV) and hips (HAV).